2024
DOI: 10.1001/jama.2024.8523
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Kidney Function After Living Kidney Donation

Amit X. Garg,
Jennifer B. Arnold,
Meaghan S. Cuerden
et al.

Abstract: ImportanceRecent guidelines call for better evidence on health outcomes after living kidney donation.ObjectiveTo determine the risk of hypertension in normotensive adults who donated a kidney compared with nondonors of similar baseline health. Their rates of estimated glomerular filtration rate (eGFR) decline and risk of albuminuria were also compared.Design, Setting, and ParticipantsProspective cohort study of 924 standard-criteria living kidney donors enrolled before surgery and a concurrent sample of 396 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Over a median of 7 years of follow-up with more than 100 000 blood pressure measurements, the authors found no difference in hypertension or albuminuria between donors and nondonor control participants, and as expected with aging, donors and nondonors had a similar average increase in systolic blood pressure. Moreover, they demonstrated that at 12 months postdonation, donors had a slower rate of decline in estimated glomerular filtration rate (eGFR) compared to nondonors . These results are encouraging and provide real-world evidence that uninephrectomy does not increase a living donor’s future risk for hypertension.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Over a median of 7 years of follow-up with more than 100 000 blood pressure measurements, the authors found no difference in hypertension or albuminuria between donors and nondonor control participants, and as expected with aging, donors and nondonors had a similar average increase in systolic blood pressure. Moreover, they demonstrated that at 12 months postdonation, donors had a slower rate of decline in estimated glomerular filtration rate (eGFR) compared to nondonors . These results are encouraging and provide real-world evidence that uninephrectomy does not increase a living donor’s future risk for hypertension.…”
mentioning
confidence: 91%
“…The gap addressed, however, is much smaller than we hoped. While impressive in duration, follow-up, and robustness of nondonor controls, the Garg et al study is hampered by an ethnically and racially homogenous donor population, with only 14 of 954 donors identifying as Black, that no longer reflects modern-day living kidney donor populations as the study cohort had a median BMI (calculated as weight in kilograms divided by height in meters squared) of 26 and 25 among donors and nondonor controls, respectively . This lack of generalizability is poignant as hypertension has been recognized as a precursor and cause of future kidney failure .…”
mentioning
confidence: 97%
See 1 more Smart Citation